Curriculum Management to Improve Learning Quality in Early Childhood Education - Baiq Masniati; Imamah Imamah; Popon Widaningsih (Journal of Scientific Research, Education, and Technology (JSRET), 2026)
The quality of learning in early childhood education is strongly influenced by appropriate curriculum management that aligns with children’s developmental stages. Curriculum management is an essential factor in creating effective, structured, and meaningful learning processes. This study aims to analyze curriculum management in improving the quality of learning in early childhood education. The research employed a qualitative approach with a descriptive design. The research subjects included teachers and the principal at an early childhood education institution. Data were collected through observation, interviews, and documentation, while data analysis was conducted through data reduction, data display, and conclusion drawing. The findings revealed that curriculum management was implemented through three main stages: planning, implementation, and evaluation of learning activities. Planning was carried out by preparing learning instruments adjusted to children’s developmental needs. The implementation of learning was conducted flexibly and child-centered through a play-based learning approach. Evaluation was conducted continuously by emphasizing the overall developmental progress of children. The implementation of effective curriculum management contributed positively to improving the quality of learning in early childhood education.